Persuasion with correlation neglect: a full manipulation result - Levy, G; Moreno De Barreda, I; Razin, R (American Economic Association, 2022)
We consider an information design problem in which a sender tries to persuade a receiver that has "correlation neglect," i.e., fails to understand that signals might be correlated. We show that a sender with unlimited number of signals can fully manipulate the receiver. Specifically, the sender can induce the receiver to hold any state-dependent posterior she wishes to. If the sender only wishes to induce a state-independent posterior, she can use fully correlated signals, but generally she needs to design more involved correlation structures.